PENGGUNAAN MEDIA ANIMASI PADA PEMBELAJARAN PAI UNTUK MENINGKATKAN MOTIVASI BELAJAR TUNAGRAHITA - Nilna Azizatus Shofiyyah; Asep Nursobah; Tarsono Tarsono (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2020)
The purpose of this study to explain the validation, implementation, factors, and effectiveness of animation media products in Islamic Religious Education Learning to improve learning motivation for children with developmental disabilities in SLB Angkasa Lanud Sulaiman. This type of research is a qualitative case study approach, taking place in SLB Angkasa Lanud Sulaiman. The results showed: 1) The validation of animated media products in Islamic learning PAI material was 94.1 and 91.4 If converted into an evaluation table the results of expert trials included in the